2004
DOI: 10.22358/jafs/70283/2004
|View full text |Cite
|
Sign up to set email alerts
|

Linseed-based diets for sheep. 1. Nutrient digestibility, N retention and rumen fermentation

Abstract: The effects of linseed-based diets for sheep on nutrient digestibility, N retention and some parameters in blood serum and rumen fluid were studied. Linseed-based diets contained more fat (%) and different farty acid profiles. Inclusion of linseed increased crude fat digestibility from 68 to 80% (PO.05), without significant effects on digestibility of other nutrients and N retention. Statistically significant differences (PO.05) were found in the total cholesterol, triacylglyceride and total lipid contents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Moreover, at first cut, 75 kg/ha of seed rate (10.19 MJ/kg) had significantly higher metabolisable energy (ME) than 90 kg/ha seed rate (10.15 Furthermore, because metabolisable energy is proportional to digestible energy and differences in digestible energy result in differences in metabolisable energy. Micek et al (2004) and Gill et al (2013) both reported similar findings. Increased seed rates led to drop in RFV, RFQ and NEL while DMD and DMI values fell.…”
Section: Impact Of Agronomic Management Practices On Quality and Prod...supporting
confidence: 61%
“…Moreover, at first cut, 75 kg/ha of seed rate (10.19 MJ/kg) had significantly higher metabolisable energy (ME) than 90 kg/ha seed rate (10.15 Furthermore, because metabolisable energy is proportional to digestible energy and differences in digestible energy result in differences in metabolisable energy. Micek et al (2004) and Gill et al (2013) both reported similar findings. Increased seed rates led to drop in RFV, RFQ and NEL while DMD and DMI values fell.…”
Section: Impact Of Agronomic Management Practices On Quality and Prod...supporting
confidence: 61%
“…Linseed did not disturb rumen function (Micek et al, 2004). Probably for this reason no significant effect of linseed was found on the performance of animals and chemical composition of their products.…”
Section: Discussionmentioning
confidence: 87%